KINETICS OF DECOMPOSITION OF DOLOMITE FROM THE SHORSU DEPOSIT BY NITRIC ACID - Gulnoza Saydullayeva (Web of Journals Publishing, 2025)
The kinetics was studied process of dolomite decomposition by nitric acid depending on concentration and temperature. The main kinetic parameters of the decomposition process are established and equations are derived for the dependence of the foam multiplicity constant on the acid feed rate.
Keywords: Dolomite, Nitric acid of ethylene producers, foam multiplicity. foaming decomposition of dolomite.